Measurement Invariance of the Scale of Positive and Negative Experience Across 13 Countries. (October 2022) - Jovanović, Veljko; Joshanloo, Mohsen; Martín-Carbonell, Marta; Caudek, Corrado; Espejo, Begoña; Checa, Irene; Krasko, Julia; Kyriazos, Theodoros; Piotrowski, Jarosław; Rice, Sean P. M.; Junça Silva, Ana; Singh, Kamlesh; et al.
The Scale of Positive and Negative Experience (SPANE) is widely used to measure emotional experiences, but not much is known about its cross-cultural utility. The present study evaluated the measurement invariance of the SPANE across adult samples ( N = 12, 635; age range = 18-85 years; 58.2% female) from 13 countries (China, Colombia, Germany, Greece, India, Italy, Japan, Poland, Portugal, Serbia, Spain, Turkey, and the United States). Configural and partial scalar invariance of the SPANE were supported. Three items capturing specific negative emotions (sad, afraid, and angry) were found to be culturally noninvariant. Our findings suggest that the SPANE's positive emotion terms and general negative emotion terms (e.g., negative and unpleasant) might be more suitable for cross-cultural studies on emotions and well-being, whereas caution is needed when comparing countries using the SPANE's specific negative emotion items.